Recurrent paraganglioma of the vulva: A rare case report and review of the literature - Kong, Wenzhi; Qu, Qingxi; Zhang, Shiqian (Frontiers in Oncology, 2022)
Abstract: Purpose Vulva paragangliomas are rare and usually misdiagnosed or missed, especially in juveniles. Our aim was to summarize the clinical characteristics and treatments of vulva paragangliomas. Methods and results We present a case of a 17-year-old Chinese patient with functional paraganglioma from the vulva that was misdiagnosed as clear cell carcinoma. She had suffered from severe headaches, palpitations, sweating, pallor and hypertension. The vaginal wall was invaded by this mass. The tumour was surgically removed smoothly. However, the disease recurred 7 years after surgery, and the patient was treated again. Personalized genetic testing was performed while recovering, and the results suggested that the patient had a germline mutation in the Succinate Dehydrogenase subunit B (SDHB) gene. Now, the patient has been discharged successfully, her blood pressure has returned to normal and some of her clinical symptoms disappeared. A review of the literature concerning the topic is also presented, there have been only 2 cases of paraganglioma of the vulva and 11 cases of vaginal paraganglioma since 1955. Conclusion Our case describes a recurrent vulvovaginal paraganglioma with SDHB gene mutation and the largest tumor diameter to date. The diagnosis and treatment process of this case can provide reference for the management of other similar patients.